Thermodynamic Assessment of the NaF-KF-UF4 System - Bianca Schacherl; Rachel Eloirdi; Rudy J. M. Konings; Ondrej Beneš (Thermo, 2021)
In the Molten Salt Reactor (MSR) concept, metal fluorides are key components of possible fuel and coolant salts. The fast reactor option opens the possibility for alternatives to the Li based matrix salts, avoiding the costly 7Li enrichment and the tritium production from residual 6Li. Such alternatives can be based on NaF and KF as matrix components. In this study, two pseudo-binary phase diagrams of NaF-UF4 and KF-UF4, and the NaF-KF-UF4 pseudo-ternary system were experimentally investigated using Differential Scanning Calorimetry (DSC). The obtained data were used to perform a full thermodynamic assessment of the NaF-KF-UF4 system. The calculated pseudo-ternary eutectic was found at 807 K and a 68.9-7.6-23.5 mol% NaF-KF-UF4 composition. The comprehensive experimental and modelling data obtained in this work provide further extension of the JRCMSD thermodynamic database describing thermodynamic properties of key fuel and coolant salts for the MSR technology.